Cuγ (γ = 1–3)-Modified MoS2 Monolayer as a Gas Sensor for Detecting C4F7N and Its Decomposition Components - Changyun Li; Peigang Chen; Yongjin Yu; Chuanyang Li (Nanomaterials, 2022)
Perfluorinated isobutyronitrile (C4F7N) is favored in electrical engineering because it is an environmentally friendly gas-insulating medium with a low greenhouse effect. Unfortunately, under the influence of electricity and over-heating, its decomposition results in the deterioration of its insulating properties, which potentially leads to partial discharge or even gas breakdown. In this paper, the adsorption behavior of C4F7N gas and its toxic decomposition product, acetonitrile (C2N2), on MoS2 surfaces doped with small copper clusters was investigated by calculating the adsorption energy and density of states, etc. The effects of multiple initial adsorption positions as well as externally applied electric fields were also taken into account. The results depict that the maximum adsorption energy of C4F7N on the Cuγ (γ = 1–3)-MoS2 surface gradually decreases with the increase in γ. The Cu3-modified MoS2 is most suitable for use as a resistive-based gas-sensitive sensor substrate. This paper provides the theoretical foundation for the maintenance of future power equipment with environmentally friendly insulating gas.